Journeys to the spiritual lands : the natural history of a West Indian religion - Zane, Wallace W. (Wallace Wayne), 1964- (Oxford University Press, 1999)
Although much has been written on the Afro-Catholic syncretic religions of Vodou, Candomble, and Santeria, the Spiritual Baptists--an Afro-Caribbean religion based on Protestant Christianity--have received little attention. This work offers the first detailed examination of the Spiritual Baptists or "Converted". Based on 18 months of fieldwork on the Island of St. Vincent (where the religion arose) and among Vincentian immigrants in Brooklyn, Zane's analysis makes a contribution to the literature on African-American and African Diaspora religion and the anthropology of religion more